Arktoalpínská tundra Krkonoš - Štursa, Jan , 1943-
Long-term multidisciplinary research has significantly advanced our understanding of the Krkonoše Mts. arctic-alpine tundra. Three tundra zones (cryo-eolian, cryo-vegetated and niveo-glaciated) are recognized and can be found on the highest summits, etchplains of the western and eastern parts of the mountains and in glacial cirques on both sides of the state border. The arcticalpine tundra of the Krkonoše Mts. is one of the major centres of geobiodiversity in the context of Central European mountains. Jan Štursa.